‘Adult Learning Theories’ & its Application in the Re-accreditation Journey of Physician Migrants: A Review - Malek, Sharafat; Talukder, Md Humayun Kabir (Bangladesh Journal of Medical Education, 2018)
Literature on learning among immigrant adults is limited.1, 2 Published literatures directly concerning the socio-cultural educational experiences of permanent resident international medical graduates (PRIMGs) at their post-migration adaptive period is even more limited.3 In order to properly understand the post-migrational re-qualifying experiences of PRIMGs; it was felt important to study and incorporate educational theories. This paper has focused on examining some of the adult learning theories that underpin PRIMGs' accreditation experiences in developed English-speaking countries i.e. Australia. To do this has involved repeatedly visiting a range of educational theories, concepts and paradigms. Since one single theory or paradigm failed to cover all aspects of the study, it was deemed important to explore a variety of different theories. Although the social experience during re-settlement is crucially important for predicting PRIMGs' academic progress; this paper solely concentrates on their post-migration educational experiences. The review has suggested that some preknowledge on nature of the educational facilities in the host country is important for re-establishing medical career. For some, this process may all go smoothly whereas others may find this journey difficult, frustrating and costly. The outcome of settlement ought to be better if the decision to migrate was taken with pre-knowledge of the post-migration learning environment and structure4; although, many other micro and macro elements are equally involved in the process. The implementation and practice of 'Experiential learning model' has been advocated that both indicates and emphasizes the need for funded arrangements of 'Structured on the job training' programs for PRIMGs. The alternate option would be to undertake full-fee-paid, practical-oriented, up-skilling bridging courses6. Such training would assist them to effectively complete their learning cycle and re-qualify in a shorter timeframe. Bangladesh Journal of Medical Education Vol.9(2) 2018: 27-31